Novel lamin B receptor mutation (c.561C > G) in a patient with Pelger-Huët anomaly: a case report - Yin, Jiaojiao; Huang, Dan; Liu, Zhenya; Zhu, Enpeng; Zhang, Chong; Wang, Linyan; Li, Bing (Frontiers in Pediatrics, 2025)
Pelger-Huët anomaly (PHA), an autosomal dominant disorder characterized by abnormal granulocyte morphology, was first described in 1928. Mutations in the lamin B receptor (LBR) gene cause a phenotypic spectrum ranging from isolated PHA, PHA with mild skeletal abnormalities, to the embryonic-lethal Greenberg skeletal dysplasia. We report a Chinese boy presenting peripheral blood granulocyte abnormalities associated with a novel LBR gene mutation. Whole-exome sequencing uncovered the LBR gene heterozygous mutation, NM_194442.2: c.561C > G (p.Tyr187*). Notably, the patient exhibited scoliosis secondary to hemivertebrae, potentially representing a previously unreported skeletal manifestation of mutations in the LBR gene. Analyzing the differential diagnosis between PHA, immature granulocytes, and pseudo-PHA, along with elucidating genotype-phenotype correlations for LBR mutations, is crucial for advancing our understanding of PHA and related disorders.